3'UTR of mRNA Encoding CPEB Protein Orb2 Plays an Essential Role in Intracellular Transport in Neurons. - Kozlov, E.N.; Deev, R.V.; Tokmatcheva, E.V.; Tvorogova, A.; Kachaev, Z.M.; Gilmutdinov, R.A.; Zhukova, M.; Savvateeva-Popova, E.V.; Schedl, P.; Shidlovskii, Y.V. (Cells, 2023)
Intracellular trafficking plays a critical role in the functioning of highly polarized cells, such as neurons. Transport of mRNAs, proteins, and other molecules to synaptic terminals maintains contact between neurons and ensures the transmission of nerve impulses. Cytoplasmic polyadenylation element binding (CPEB) proteins play an essential role in long-term memory (LTM) formation by regulating local translation in synapses. Here, we show that the 3'UTR of the Drosophila CPEB gene orb2 is required for targeting the orb2 mRNA and protein to synapses and that this localization is important for LTM formation. When the orb2 3'UTR is deleted, the orb2 mRNAs and proteins fail to localize in synaptic fractions, and pronounced LTM deficits arise. We found that the phenotypic effects of the orb2 3'UTR deletion were rescued by introducing the 3'UTR from the orb, another Drosophila CPEB gene. In contrast, the phenotypic effects of the 3'UTR deletion were not rescued by the 3'UTR from one of the Drosophila ?-tubulin genes. Our results show that the orb2 mRNAs must be targeted to the correct locations in neurons and that proper targeting depends upon sequences in the 3'UTR.